Strategies based on organ decellularization and recellularization. (17th June 2019) - Hillebrandt, Karl H.; Everwien, Hannah; Haep, Nils; Keshi, Eriselda; Pratschke, Johann; Sauer, Igor M.
Summary: Transplantation is the only curative treatment option available for patients suffering from end‐stage organ failure, improving their quality of life and long‐term survival. However, because of organ scarcity, only a small number of these patients actually benefit from transplantation. Alternative treatment options are needed to address this problem. The technique of whole‐organ decellularization and recellularization has attracted increasing attention in the last decade. Decellularization includes the removal of all cellular components from an organ, while simultaneously preserving the micro and macro anatomy of the extracellular matrix. These bioscaffolds are subsequently repopulated with patient‐derived cells, thus constructing a personalized neo‐organ and ideally eliminating the need for immunosuppression. However, crucial problems have not yet been satisfyingly addressed and remain to be resolved, such as organ and cell sources. In this review, we focus on the actual state of organ de‐ and recellularization, as well as the problems and future challenges.